#### Answer

Correct

#### Work Step by Step

$6(2x-3)+5=12x-18+5\rightarrow$ apply the distributive property
$12x-18+5=12x-18+5$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

Correct

$6(2x-3)+5=12x-18+5\rightarrow$ apply the distributive property
$12x-18+5=12x-18+5$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.